The female voice - Abitbol, Jean (Plural Publishing, 2019)
All you ever wanted to know about the female voice but you never dared to ask by the leading world expert, Dr. Jean Abitbol! Enriched with numerous fascinating anecdotes, this exciting book covers the journey of the female voice and its development and impact on others from motherhood to old age. And the journey is full of surprises with answers to fascinating questions. Does voice have a sex? Is that voice sexual or hormonal? Is it genetic or epigenetic? Why do female voices change less at puberty than men''s voices? How does a woman''s voice change during her menstrual cycle? Is the female biological clock still a mystery? How and why is the voice the target of the sexual hormones? What kind of treatments are we using today---from contraceptive pills, hormonal replacement therapy to alternative medicine---that affect the voice and how do they affect it? Is a woman''s voice damaged after the hormonal "earthquake" that takes place when she is in her fifties? Could we avoid or prevent the aging voice in women? What are the specific pathologies affecting the female vocal folds? What are the links between diet, hygiene, and exercise, and how do they affect the female voice? Like a ship on the waves of the sea of life, the female voice, a life-space-time continuum, travels through the winds of emotion and hormonal changes brought about by aging. Dr. Jean Abitbol guides the reader through these changes, mapping the female voice's journey through life. With his guidance, you will come to see and to understand the emotion, the power, the seduction, the force, and the charm of the female voice and how they converge to make up the female persona